A prospective randomized trial to compare side effects of early versus late removal of Foley’s catheter and vaginal pack following vaginal hysterectomy - Gupta, Ayesha; P., Reddi Rani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: There is a controversy about the ideal time for removal of catheter and vaginal pack following vaginal hysterectomy. The present study was undertaken to compare post-operative morbidity in early and late removal of Foley’s catheter and vaginal pack. The aim of this study is to compare post-operative morbidity in early and late removal of Foley’s catheter and vaginal pack following vaginal hysterectomy. Methods: This was a prospective randomized study with n=100 of those women who were undergoing vaginal hysterectomy with or without pelvic floor repair and fulfilled the inclusion criteria. After informed written consent, they were assigned to Foley’s catheter and vaginal pack removal group in 6 hours (group I, n=50) or 24 hours removal group (group II, n=50). Primary parameters used to assess were urine routine and microscopy, urine culture and sensitivity on post-operative day 2, need for re-catheterization and repacking, febrile morbidity, ambulation, vault infection and post-operative hospital stay duration were analyzed in both groups. Results: Febrile morbidity was found in 6% and 8%, Positive urine culture was found in 10% and 20%, Rate of re-catheterization was 10% in group I and group II respectively. Vaginal bleeding after pack removal and repacking was in 6% in group I whilst none had in group II. Conclusions: Early removal was associated with less incidence of urinary tract infection, and increased rate of re-catheterization and repacking. Needs larger comparative studies to support the practice of early removal.